Estudio de los programas del fin de semana de Radio Stereo Macará 104.5 y la aceptación de la audiencia macareña - Díaz Vaca, María Luisa (2024)
The study of media reception of weekend programs on Radio Stereo Macará (104.5) in the province of Loja in Ecuador and the acceptance of the Macareña audience aged between 20 and 39 years old, aims to investigate their consumption preferences of this traditional media, with interest in weekend programming. For this purpose, a methodology with a mixed approach was applied in order to propose a pilot program aimed at the young audience of the Macará canton, taking into account their preferences. The studied audience is divided between two of the urban parishes of the canton, Eloy Alfaro and San Antonio de Macará, whose sample was 72 inhabitants of the canton Macará. Among the results obtained, the low interactivity of the Macareños with the weekend program broadcast by Radio Stereo Macará is evident; however, listeners of the canton mentioned the need to create a new program. For the development of the proposal of a pilot program, references from an interview applied to a radio expert and the director of Radio Stereo Macará were used to collect adequate information for the writing of the new program called Verdades. Keywords: Communication and radio, Radio studies, Media, Broadcasting, Radio in Ecuador